The molecular functions of Biodentine and mineral trioxide aggregate in lipopolysaccharide‐induced inflamed dental pulp cells. (30th March 2021) - Wang, M. C.; Tu, H. F.; Chang, K. W.; Lin, S. C.; Yeh, L. Y.; Hung, P. S.
Abstract: Aim: To explore the proliferation, adhesion and differentiation response and the underlying mechanisms that occur in lipopolysaccharide (LPS)‐induced inflamed dental pulp cells (DPCs) in contact with Biodentine and mineral trioxide aggregate (MTA). Methodology: The DPCs were isolated from three healthy donors and named DPC‐H1 to DPC‐H3. The DPCs were pre‐cultured with 2 or 5 μg mL −1 LPS for 24 h to induce inflammation. The expression of inflammation marker miR‐146a was detected by q‐PCR. The normal and LPS‐induced DPCs were further treated with 0.14 mg mL −1 Biodentine or 0.13 mg mL −1 MTA for 24 h. MTT assay and adhesion assay were used to analyse the changes of cell phenotypes. DSPP, AKT and ERK expressions were detected by Western blotting. The data were analysed by Mann–Whitney test or two‐way anova . Differences were considered statistically significant when P  < 0.05. Results: In LPS‐induced DPCs, Biodentine and MTA treatment neither induced nor aggravated LPS‐induced inflammation, but their presence did increase the expression of the odontogenic differentiation marker DSPP. Under 2 or 5 μg mL −1 LPS‐induced inflammation, Biodentine and MTA promoted the proliferation of DPC cells, and significantly in DPC‐H2 ( P  < 0.0001 for both reagents). With the treatment of 2 μg mL −1 LPS, the cell adhesion of DPCs on the fibronectin‐coated culture plates was increased significantly by Biodentine ( P  = 0.0413) and MTA ( P  < 0.0001). Biodentine and MTA regulated cell adhesion on the fibronectin‐coated culture plates ( P  < 0.0001 for both reagents) and proliferation ( P  < 0.0001 for both reagents) via the AKT pathway. However, the AKT pathway was not involved in the expression of DSPP induced by Biodentine and MTA. Conclusion: Biodentine and MTA enhanced the proliferation, adhesion and differentiation of LPS‐induced DPCs. The proliferation and adhesion process induced by Biodentine and MTA was via the AKT pathway. However, the cellular differentiation process might not use the same pathway, and this needs to be explored in future studies.